Проект словника обрядових фразеологізмів східнослобожанських говірок - Царьова, І. (Лексикографічний бюлетень, 2011)
The article deals with ethnic and cultural features of the semantics of ritual phraseologisms of easternslobozhshanskiy dialect. Actuality of research is due to the necessity to create ritual phraseological dictionary, focuses on search patterns of synchronic ethnographic nominations and traced slices. The foundamental base is lexical author ritual contexts, numbering about 750 items, collected and arranged field method, the registry phrasebook eastern slobozhshanskiy and eastern- velds dialects of Donbass by V. Uzhchenko and D. Uzhchenko (2005), large volume (1008 p.). work “Life and Creativity of pagans of Kharkiv province: Essays on ethnography of the region” edited by V. Ivanov (1898). The proposed research focused on solving one of the most fundamental issues of linguistics is phraseological derivation in ethno cultural space of East Slobozhanshchina. Proves that the formation of semantic values of ritual phraseologicals are involving all aspects of its importance, the priority of which is denotative aspect.